Grain boundary braiding precursor, positive electrode material and preparation method

By weaving nanooxides on the grain boundary of the positive electrode material to form a stable sandwich structure, the problem of structural cracking and irreversible phase change in the long cycle of the positive electrode material is solved, the cycle stability and life of the lithium battery are improved, and Simplified the preparation process.

CN116395759BActive Publication Date: 2024-12-27JINGHE NEW TOWN SHAANXI COAL TECH RES INST NEW ENERGY MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310399198.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-14
Publication Date
2024-12-27
Estimated Expiration
2043-04-14

AI Technical Summary

Technical Problem

Existing positive electrode materials are prone to particle cracking and irreversible phase change during long cycles, resulting in material capacity loss and structural degradation, affecting the cycle stability and life of lithium batteries.

Method used

Using the method of weaving precursors in grain boundaries, nano oxides are weaved onto the grain boundaries of the precursor to form a sandwich structure, and a uniform nanotitanium dioxide braided layer is formed through co-precipitation and micro-oxidation technology to improve the interface stability and electricity of the material. Chemical properties.

Benefits of technology

It effectively alleviates the internal structure cracking of high-nickel positive electrode materials under long cycles, reduces irreversible phase change and manganese dissolution, improves Li+ diffusion capacity and material circulation stability, extends the life of lithium batteries, and simplifies the preparation process. Reduced production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116395759B_ABST
    Figure CN116395759B_ABST
Patent Text Reader

Abstract

The present invention discloses a grain boundary braided precursor, comprising a sandwich structure formed by a precursor core, a nano-oxide braided layer and a precursor shell. The present invention also discloses a preparation method of the above-mentioned precursor, and the present invention also discloses a positive electrode material made by using the above-mentioned precursor. The precursor provided by the present invention braids the nano-oxide onto the grain boundary of the precursor, improves the interface stability of the positive electrode material, and improves the electrochemical performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery materials, relates to a grain boundary braiding precursor, and also relates to a preparation method of the precursor. Background Art

[0002] The positive electrode material is the core component of lithium batteries and has a direct impact on many core performance indicators of lithium batteries, including capacity, life, rate, safety, etc. Usually, the lithium ions that can be intercalated and deintercalated in lithium batteries are derived from the positive electrode active material. At present, there are three major development directions for ternary positive electrode materials, namely single crystal, high voltage, and high nickel. Whether it is ordinary positive electrode materials or when developing in the direction of single crystal, high voltage, and high nickel, doping and surface modification are effective methods to improve the comprehensive performance of positive electrode materials. And the doping and modification methods are also one of the core competitiveness of positive electrode material companies. Doping elements include Al, Mg, Cr, etc., and the improvement mechanism includes stabilizing the main structure, increasing the lithium ion layer spacing, and segregation at the grain boundary. Commonly used coating agents include Al2O3, V2O5, ZnO, ZrO2, TiO2, MgO, etc.

[0003] The ternary precursor is the key raw material for achieving the performance of the ternary cathode material. The coating of the ternary cathode material can be achieved by coating the ternary precursor. The existing technical method for preparing the precursor coating layer is to generate a new coating layer on the surface of the secondary particles of the precursor by co-precipitation of the coating elements. The size and uneven arrangement of the newly generated primary particles will affect the Li + The surface coating will also affect the conductivity of the material. At the same time, during the long-term cycle of the battery, cracks will occur on the surface of the particles and may extend to the inner core. The side reactions with the electrolyte will cause irreversible phase changes on the surface and crack interface, resulting in material capacity loss and structural degradation.

[0004] Nano-titanium dioxide has high chemical stability, thermal stability and super hydrophilicity, and the surface of the ternary precursor has a large number of active sites and a high specific surface energy, which makes it easy for precipitates to attach and grow, thereby forming a uniformly distributed coating layer on the surface of the ternary precursor. Therefore, an appropriate amount of nano-titanium dioxide can be coated during the preparation of the ternary precursor to reduce the stress between particles and the tiny structural and volume strains caused during the cycle, thereby improving the cycle stability of lithium battery materials during the charge and discharge process, improving the electrochemical properties of battery materials, and extending the life of lithium batteries. Summary of the invention

[0005] The purpose of the present invention is to provide a grain boundary braiding precursor, which braids nano oxides onto the grain boundaries of the precursor, improves the interface stability of the positive electrode material, and enhances the electrochemical performance of the material.

[0006] The second object of the present invention is to provide a method for preparing a grain boundary braiding precursor.

[0007] The third object of the present invention is to provide a method for making positive electrode materials using grain boundary braiding precursors.

[0008] The first technical solution adopted by the present invention is a grain boundary braided precursor, which includes a sandwich structure formed by a precursor core, a nano-oxide braided layer and a precursor shell.

[0009] The first technical solution of the present invention is also characterized in that:

[0010] The molecular formula of the precursor is: M(OH)2, where M is selected from Ni, Co, Mn, Al, Fe, Cu and OH - One or more elements that form hydroxide precipitates.

[0011] The particle size of the precursor is 3 to 20 μm; the specific surface area of ​​the precursor is 10 to 14 m 2 / g; the tap density of the precursor is 1.9~2.2g / cm 3 ;

[0012] The core particle size of the precursor is 1.2-10.0 μm; the thickness of the nano-oxide braided layer is 0.6-5.0 μm.

[0013] The second technical solution adopted by the present invention is a method for preparing a grain boundary braiding precursor, which specifically comprises the following steps:

[0014] Step 1, according to the molar ratio of all elements in the precursor M(OH)2, prepare 2.0-8.0 mol / L mixed salt solution A, 5.0-10.0 mol / L sodium hydroxide solution B and 3.0-13.0 mol / L ammonia solution C;

[0015] Step 2, adding pure water, sodium hydroxide solution B and ammonia solution C into the reaction kettle to prepare a reaction base liquid, and introducing nitrogen;

[0016] Step 3, keeping nitrogen flowing, adding the prepared mixed salt solution A, sodium hydroxide solution B and ammonia solution C to the bottom liquid of the reactor in parallel to perform a coprecipitation reaction, controlling the reaction temperature and reaction pH, and forming a precursor core in the reactor;

[0017] Step 4, when the precursor core particle size reaches the target value, stop adding solution A, solution B and solution C to the reactor, switch nitrogen to air, and carry the nano-oxide into the reactor at a fixed flow rate by air. Under the micro-oxidation of air, the primary particles become thinner and the pores become more, forming a grain boundary nano-oxide braided layer. When the nano-oxide braided layer reaches the set thickness, stop adding nano-oxide and switch to nitrogen;

[0018] Step 5, solution A, solution B and solution C are continuously fed and reacted to form a precursor shell, and the nano-oxide braided layer is wrapped in the middle of the particle, until the precursor particle size reaches the target particle size, the reaction feeding is stopped, and stirring and aging are continued for 3 to 4 hours;

[0019] Step 6, the material aged in step 5 is subjected to solid-liquid separation, washing, and drying, and a precursor having nano-oxide grain boundary weaving is obtained after screening and demagnetization.

[0020] The second technical solution of the present invention is also characterized in that:

[0021] In step 1, the mixed salt solution A is at least one of sulfate, acetate, nitrate and chloride.

[0022] In step 4, the air flow rate carrying the nano-oxide is 100-300 mL / min; the nano-oxide is nano-titanium dioxide with super hydrophilicity.

[0023] The reaction conditions in the precursor preparation process are: at a temperature of 55-65°C, a stirring speed of 450-600±5rpm, a pH value of 10.50-12.00, and an ammonia concentration of 0.15-0.45mol / L until the particle size D50 of the precursor reaches the target value.

[0024] The third technical solution adopted by the present invention is that the precursor and the lithium salt are mixed and sintered to obtain the product.

[0025] The third technical solution of the present invention is also characterized in that:

[0026] The molar ratio of the precursor to the lithium source is 0.95-1.10, and the sintering is carried out at 650-800° C. for 10-30 hours in an oxygen atmosphere.

[0027] The beneficial effects of the present invention are as follows:

[0028] 1. The present invention increases the specific surface area by micro-oxidation of the core of the precursor, and at the same time weaves nano-titanium dioxide at the grain boundary of the core to ensure the high tap density of the precursor.

[0029] 2. The grain boundary braided precursor prepared by the present invention is protected by the nano-titanium dioxide braided layer, which alleviates the internal structure cracking of the high-nickel positive electrode material under long-term cycling, while protecting it from electrolyte corrosion, reducing the occurrence of irreversible phase change, and inhibiting the dissolution of manganese in the active material under high voltage. In addition, the uniform nano-titanium dioxide braided layer also reduces the internal impedance of the electrode, improving the Li + diffusion.

[0030] 3. The nano-titanium dioxide grain boundary braided precursor prepared by the present invention has uniform particle size distribution, good primary particle uniformity, and neat arrangement. The positive electrode material obtained after mixed lithium calcination has high interface stability and improved cycle stability.

[0031] 4. The present invention performs nano-titanium dioxide grain boundary weaving during the precursor preparation process, does not add additional reaction containers, and does not require pre-treatment of raw materials, which simplifies the preparation process, reduces production costs, and the prepared materials have excellent performance. These results show that the nano-titanium dioxide braided layer strategy provides great opportunities for inspiring advanced high-energy density positive electrodes for lithium-ion batteries and applying them to large-scale power sources. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a schematic structural diagram of the grain boundary braiding precursor of the present invention;

[0033] 2(a) and (b) are SEM images of a nano-titanium dioxide braided layer and a final precursor material obtained during the preparation process of Example 1 of the method for preparing a grain boundary braided precursor of the present invention;

[0034] Figure 3 (a) and (b) are SEM images of the nano titanium dioxide braided layer and the final precursor material obtained during the preparation process of Comparative Example 1;

[0035] Figure 4 (a) and (b) are SEM images of the precursor material prepared in Comparative Example 2;

[0036] Figure 5 The cycle data diagram of the positive electrode materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 (3.0-4.3 V, 0.1 C, 100 cycles). DETAILED DESCRIPTION

[0037] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0038] The grain boundary braiding precursor of the present invention is as follows Figure 1 As shown, it has a three-layer structure, including a sandwich structure formed by a precursor core, a nano-oxide woven layer and a precursor shell.

[0039] The molecular formula of the precursor is: M(OH)2, where M is selected from Ni, Co, Mn, Al, Fe, Cu and OH - One or more elements that form hydroxide precipitates.

[0040] The particle size of the precursor is 3 to 20 μm.

[0041] The core particle size of the precursor is 1.2 to 10.0 μm.

[0042] The thickness of the nano-oxide braided layer is 0.6-5.0 μm.

[0043] The specific surface area of ​​the precursor is 10.00~14.00m 2 / g.

[0044] The tap density of the precursor is 1.90~2.20g / cm 3 .

[0045] The method for preparing a grain boundary braiding precursor of the present invention comprises the following steps:

[0046] Step 1, according to the molar ratio of all elements in the precursor M(OH)2, prepare 2.0-8.0 mol / L mixed salt solution A, 5.0-10.0 mol / L sodium hydroxide solution B and 3.0-13.0 mol / L ammonia solution C;

[0047] The mixed salt solution A is a mixture of one or more of sulfate, acetate, nitrate and chloride.

[0048] Step 2, adding pure water, sodium hydroxide solution B and ammonia solution C into the reaction kettle to prepare a reaction base liquid, and introducing nitrogen;

[0049] Step 3, keeping nitrogen flowing, adding the prepared mixed salt solution A, sodium hydroxide solution B and ammonia solution C to the bottom liquid of the reactor in parallel to perform a coprecipitation reaction, controlling the reaction temperature and reaction pH, and forming a precursor core in the reactor;

[0050] Step 4, when the precursor core particle size reaches the target value, the addition of solution A, solution B and solution C is stopped, and the nitrogen gas is switched to air, and the air carries the nano-oxide into the kettle at a fixed flow rate. Under the micro-oxidation of the air, the primary particles become thinner and the pores become more, forming a grain boundary nano-oxide braided layer. When the braided layer reaches a certain thickness, the addition of nano-oxide is stopped and switched to nitrogen;

[0051] In step 4, the air flow rate carrying the nano-oxide is 100-300 mL / min; the nano-oxide is nano-titanium dioxide with super hydrophilicity.

[0052] Step 5, solution A, solution B and solution C are continuously fed and reacted to form a precursor shell, and the nano-oxide braided layer is wrapped in the middle of the particle, until the precursor particle size reaches the target particle size, the reaction feeding is stopped, and stirring and aging are continued for 3 to 4 hours;

[0053] The ratio of the core radius of the precursor with a nano-oxide braided layer: the braided layer thickness: the shell thickness is 2:1:2 (small particle size precursor) or 2:2:1 (conventional particle size precursor) or 2:1:1 (large particle size precursor).

[0054] Step 6, the material aged in step 5 is subjected to solid-liquid separation, washing, and drying, and a precursor having nano-oxide grain boundary weaving is obtained after screening and demagnetization.

[0055] In the process of forming the precursor according to steps 1 to 6, the reaction conditions are: at a temperature of 55 to 65°C, a stirring speed of 450 to 600±5rpm, a pH value of 10.50 to 12.00, and an ammonia concentration of 0.15 to 0.45 mol / L, the reaction is carried out until the particle size D50 of the precursor reaches the target value.

[0056] The present invention also provides a positive electrode material, which is prepared by mixing and sintering the aforementioned precursor material and a lithium salt.

[0057] The sintering process is as follows: the molar ratio of the precursor to the lithium source is 0.95-1.10, sintering is performed at 650-800° C. for 10-30 hours, and the sintering atmosphere is an oxygen atmosphere.

[0058] The present invention aims to solve the problems of poor battery cycle performance caused by particle cracking under long-term cycle due to surface coating of current positive electrode materials, side reactions between crystal surfaces and electrolytes, and irreversible phase changes. A solution to improve the problem from the precursor end is proposed, namely, a grain boundary weaving precursor, which weaves nano-oxides onto the grain boundaries of a nickel-cobalt-manganese precursor, thereby improving the interface stability of the positive electrode material and enhancing its cycle performance.

[0059] Example 1

[0060] A certain mass of NiSO4, CoSO4 and MnSO4 were weighed and dissolved in deionized water according to the molar ratio of Ni:Co:Mn=0.9:0.05:0.05 to prepare 100L of mixed salt solution with a concentration of 8mol / L, a sodium hydroxide solution with a concentration of 5mol / L and an ammonia solution with a concentration of 7mol / L.

[0061] Deionized water was added to a reactor equipped with a circulating water bath heating system, an automatic ammonia-alkali salt flow control system, and a pH automatic control system to submerge the pH meter probe. Ammonia solution was added to the reactor until the bottom liquid ammonia concentration was 0.20 mol / L. Sodium hydroxide solution was added until the bottom liquid pH was 10.85. Nitrogen was introduced at a flow rate of 2.0±0.5 L / h for 3 hours. Nitrogen was introduced throughout the formation of the precursor core and shell, and the reaction temperature was maintained at 60±1°C and the agitator speed was 500±5 rpm.

[0062] The mixed salt solution, sodium hydroxide solution and ammonia solution are added to the reactor in parallel using a peristaltic pump to start the precursor core generation process, wherein the flow rate of the mixed salt solution is fixed at 30±2mL / min, the flow rate of the sodium hydroxide solution is determined in real time according to the automatic control system, and the flow rate of the ammonia solution is added to the reactor according to the required amount at different stages.

[0063] When the particle size of the precursor core grows to 4.0±0.5μm, stop adding the mixed salt solution, sodium hydroxide solution and ammonia solution, switch nitrogen to air, adjust the air flow rate to 200mL / min, and carry the nano-titanium dioxide into the kettle by air. In this stage, the newly arranged primary particles on the surface of the precursor core are slightly oxidized, the primary particles become thinner, and the specific surface area increases. The nano-titanium dioxide carried into the kettle by the air is adsorbed on the surface of the primary particles until the precursor particles grow to 8.0±0.5μm, then switch to nitrogen, and continue to add the mixed salt solution, sodium hydroxide solution and ammonia solution into the reactor in parallel for reaction.

[0064] When it is detected that the particle size of the material in the reactor reaches D50 of 10.0±0.5 μm, the reaction feeding is stopped, and stirring and aging are continued for 3 to 4 hours.

[0065] The slurry is centrifuged and aged, the solid is washed with sodium hydroxide solution, and then rinsed with pure water at 65-75°C, the material is dried, and the precursor material is obtained after screening and demagnetization, and is sealed and stored.

[0066] The particle size distribution data of the dried qualified sample was as follows: Dmin = 5.42 μm, D10 = 7.5 μm, D50 = 10.22 μm, D90 = 13.62 μm, Dmax = 17.52 μm, and the particle size distribution span = 0.60. Tap density TD = 1.93 g / cm 3 , specific surface area BET = 11.15m 2 / g.

[0067] The positive electrode material is prepared by uniformly mixing lithium hydroxide monohydrate and the obtained precursor in a high-speed mixer at a molar ratio of 0.95:1, sintering at 800°C for 10 hours in an oxygen atmosphere, and then naturally cooling to room temperature, grinding and sieving to obtain a positive electrode material, referred to as NCM-TY955.

[0068] The obtained positive electrode material is mixed evenly with acetylene black and PVDF, coated on aluminum foil to make a positive electrode sheet, assembled into a button battery with a lithium metal sheet, a separator and an electrolyte in a vacuum glove box, and the button battery is subjected to cycle and rate performance tests.

[0069] Figures 2(a) and (b) are SEM images of the nano-titanium dioxide braided layer (Figure 2(a)) and the final precursor material (Figure 2(b)) during the preparation process of Example 1. It can be seen from the figure that the nano-titanium dioxide braided layer is evenly distributed on the precursor primary particle layer, and the primary particles on the surface of the final precursor material prepared are in the form of thin sheets and are tightly arranged.

[0070] Example 2

[0071] A certain mass of NiSO4, CoSO4 and MnSO4 were weighed and dissolved in deionized water according to the molar ratio of Ni:Co:Mn=0.6:0.1:0.3 to prepare 100L of nickel-cobalt-manganese mixed salt solution with a concentration of 4mol / L, a sodium hydroxide solution with a concentration of 10mol / L and an ammonia solution with a concentration of 13mol / L.

[0072] Deionized water was added to a reactor equipped with a circulating water bath heating system, an automatic ammonia-alkali salt flow control system, and a pH automatic control system to submerge the pH meter probe. Ammonia solution was added to the reactor until the bottom liquid ammonia concentration was 0.15 mol / L. Sodium hydroxide solution was added until the bottom liquid pH was 12.00. Nitrogen was introduced at a flow rate of 2.0±0.5 L / h for 3 hours. Nitrogen was introduced throughout the formation of the precursor core and shell, and the reaction temperature was maintained at 55±1°C and the agitator speed was 600±5 rpm.

[0073] The mixed salt solution, sodium hydroxide solution and ammonia solution are added to the reactor in parallel using a peristaltic pump to start the precursor core generation process, wherein the flow rate of the mixed salt solution is fixed at 30±2mL / min, the flow rate of the sodium hydroxide solution is determined in real time according to the automatic control system, and the flow rate of the ammonia solution is added to the reactor according to the required amount at different stages.

[0074] When the particle size of the precursor core grows to 1.2±0.2μm, stop adding the mixed salt solution, sodium hydroxide solution and ammonia solution, switch nitrogen to air, adjust the air flow rate to 100mL / min, and carry the nano-titanium dioxide into the kettle by air. In this stage, the newly arranged primary particles on the surface of the precursor core are slightly oxidized, the primary particles become thinner, and the specific surface area increases. The nano-titanium dioxide carried into the kettle by the air is adsorbed on the surface of the primary particles until the precursor particles grow to 1.8±0.2μm, then switch to nitrogen, and continue to add the mixed salt solution, sodium hydroxide solution and ammonia solution into the reactor in parallel for reaction.

[0075] When it is detected that the particle size of the material in the reactor reaches D50 of 3.0±0.5 μm, the reaction feeding is stopped, and stirring and aging are continued for 3 to 4 hours.

[0076] The slurry is centrifuged and aged, the solid is washed with sodium hydroxide solution, and then rinsed with pure water at 65-75°C, the material is dried, and the precursor material is obtained after screening and demagnetization, and is sealed and stored.

[0077] The particle size distribution data of the dried qualified sample was as follows: Dmin = 1.08 μm, D10 = 2.48 μm, D50 = 3.37 μm, D90 = 4.54 μm, Dmax = 6.65 μm, and the particle size distribution span = 0.61. The tap density TD = 2.20 g / cm 3 Specific surface area BET = 12.03m2 / g.

[0078] The positive electrode material is prepared by uniformly mixing lithium hydroxide monohydrate and the obtained precursor in a high-speed mixer at a molar ratio of 1.05:1, sintering at 750°C for 12 hours in an oxygen atmosphere, and then naturally cooling to room temperature, grinding and pulverizing, and sieving to obtain a positive electrode material, referred to as NCM-TY613.

[0079] The obtained positive electrode material is mixed evenly with acetylene black and PVDF, coated on aluminum foil to make a positive electrode sheet, assembled into a button battery with a lithium metal sheet, a separator and an electrolyte in a vacuum glove box, and the button battery is subjected to cycle and rate performance tests.

[0080] Example 3

[0081] According to the molar ratio of Ni:Co:Mn=0.6:0.2:0.2, a certain mass of NiSO4, CoSO4, and MnSO4 were weighed and dissolved in deionized water to prepare 100L of mixed salt solution with a concentration of 2mol / L, the concentration of sodium hydroxide solution was 8mol / L, and the concentration of ammonia solution was 3mol / L.

[0082] Deionized water was added to a reactor equipped with a circulating water bath heating system, an automatic ammonia-alkali salt flow control system, and a pH automatic control system to submerge the pH meter probe. Ammonia solution was added to the reactor until the bottom liquid ammonia concentration was 0.45 mol / L. Sodium hydroxide solution was added until the bottom liquid pH was 10.50. Nitrogen was introduced at a flow rate of 2.0±0.5 L / h for 3 hours. Nitrogen was introduced throughout the formation process of the precursor core and shell, and the reaction temperature was maintained at 65±1°C and the agitator speed was 450±5 rpm.

[0083] The mixed salt solution, sodium hydroxide solution and ammonia water are added to the reactor in parallel using a peristaltic pump to start the precursor core generation process, wherein the flow rate of the mixed salt solution is fixed at 30±2mL / min, the flow rate of the sodium hydroxide solution is determined in real time according to the automatic control system, and the flow rate of the ammonia solution is added to the reactor according to the required amount at different stages.

[0084] When the particle size of the precursor core grows to 10.0±0.5μm, stop adding the mixed salt solution, sodium hydroxide solution and ammonia solution, switch nitrogen to air, adjust the air flow rate to 300mL / min, and carry the nano-titanium dioxide into the kettle by air. In this stage, the newly arranged primary particles on the surface of the precursor core are slightly oxidized, the primary particles become thinner, and the specific surface area increases. The nano-titanium dioxide brought into the kettle by the air is adsorbed on the surface of the primary particles until the precursor particles grow to 15±0.5μm, then switch to nitrogen, and continue to add the mixed salt solution, sodium hydroxide solution and ammonia solution into the reactor in parallel for reaction.

[0085] When it is detected that the particle size of the material in the reactor reaches D50 of 20±0.5 μm, the reaction feeding is stopped, and stirring and aging are continued for 3 to 4 hours.

[0086] The slurry is centrifuged and aged, the solid is washed with sodium hydroxide solution, and then rinsed with pure water at 65-75°C, the material is dried, and the precursor material is obtained after screening and demagnetization, and is sealed and stored.

[0087] The particle size distribution data of the dried qualified sample was as follows: Dmin = 9.64 μm, D10 = 13.82 μm, D50 = 20.19 μm, D90 = 24.52 μm, Dmax = 29.33 μm, and the particle size distribution span = 0.53. Tap density TD = 1.90 g / cm 3 Specific surface area BET = 14.06m 2 / g.

[0088] The positive electrode material is prepared by uniformly mixing lithium hydroxide monohydrate and the obtained precursor in a high-speed mixer at a molar ratio of 1.10:1, sintering at 650°C for 30 hours in an oxygen atmosphere, and then naturally cooling to room temperature, grinding and pulverizing, and sieving to obtain a positive electrode material, referred to as NCM-TY622.

[0089] The obtained positive electrode material is mixed evenly with acetylene black and PVDF, coated on aluminum foil to make a positive electrode sheet, assembled into a button battery with a lithium metal sheet, a separator and an electrolyte in a vacuum glove box, and the button battery is subjected to cycle and rate performance tests.

[0090] Comparative Example 1

[0091] A grain boundary braided precursor, which differs from Example 1 in that the gas used to bring nano titanium dioxide into the reactor is nitrogen, and the precursor is prepared. The particle size distribution data of the dried qualified sample is: Dmin = 6.29 μm, D10 = 8.48 μm, D50 = 11.18 μm, D90 = 14.87 μm, Dmax = 17.52 μm, and the particle size distribution span = 0.57. The tap density TD = 2.05 g / cm 3 Specific surface area BET = 10.87 m 2 / g.

[0092] The positive electrode material is prepared by uniformly mixing lithium hydroxide monohydrate and the obtained precursor in a high-speed mixer at a molar ratio of 0.95:1, sintering at 800°C for 10 hours in an oxygen atmosphere, and then naturally cooling to room temperature, grinding and sieving to obtain a positive electrode material, referred to as NCM-TY955.

[0093] The obtained positive electrode material is mixed evenly with acetylene black and PVDF, coated on aluminum foil to make a positive electrode sheet, assembled into a button battery with a lithium metal sheet, a separator and an electrolyte in a vacuum glove box, and the button battery is subjected to cycle and rate performance tests.

[0094] Figures 3(a) and (b) are SEM images of the nano-titanium dioxide braided layer (Figure 3(a)) and the final precursor material (Figure 3(b)) during the preparation process of Comparative Example 1. It can be seen from the figure that the nano-titanium dioxide braided layer is evenly distributed on the precursor primary particle layer, and the primary particles on the surface of the final precursor material prepared are thick plate-like and tightly arranged.

[0095] Comparative Example 2

[0096] A grain boundary braided precursor, which differs from Example 1 in that: there is no nano titanium dioxide braided layer, and a pure precursor is prepared. The particle size distribution data of the dried qualified sample is: Dmin = 6.85 μm, D10 = 8.71 μm, D50 = 11.38 μm, D90 = 15.11 μm, Dmax = 17.52 μm, and the particle size distribution span = 0.56. The tap density TD = 1.98 g / cm 3 Specific surface area BET = 11.57 m 2 / g.

[0097] The positive electrode material is prepared by mixing lithium hydroxide monohydrate and the obtained precursor in a high-speed mixer at a molar ratio of 0.95:1, sintering at 800°C for 10 hours in an oxygen atmosphere, and then naturally cooling to room temperature, grinding and pulverizing, and sieving to obtain the positive electrode material, referred to as NCM.

[0098] The obtained positive electrode material is mixed evenly with acetylene black and PVDF, coated on aluminum foil to make a positive electrode sheet, assembled into a button battery with a lithium metal sheet, a separator and an electrolyte in a vacuum glove box, and the button battery is subjected to cycle and rate performance tests.

[0099] 4(a) and (b) are SEM images of the nano-titanium dioxide braided layer (Fig. 4(a)) without nano-titanium dioxide during the preparation process of Comparative Example 2 and the final precursor material (Fig. 4(b)).

[0100] As can be seen from the figure, the prepared precursor material is spherical particles of uniform size, and its primary particles are flake-like and densely arranged.

[0101] In order to verify the progress of the embodiments of the present application, the button-type batteries obtained in the embodiment 1, the comparative example 1 and the comparative example 2 were subjected to cycle performance tests. The results are shown in Table 1. The curve of the discharge capacity of the button-type battery for 100 cycles and the cycle number is shown in Table 1. Figure 5 shown.

[0102] Table 1 Electrochemical performance parameters of button cell

[0103]

[0104] It can be seen from Table 1 that, compared with the precursor material coated with nitrogen and the uncoated precursor material, the precursor prepared by the technical solution provided by the present invention has a higher capacity retention rate of the button battery assembled after being calcined into the positive electrode material. Figure 5 It can be seen that after the precursor prepared by the technical solution provided by the present invention is calcined into a positive electrode material, the cycle stability and cycle durability of the button battery assembled therefrom are more advantageous.

Claims

1. A method for preparing a grain boundary braiding precursor, characterized in that: The grain boundary braided precursor comprises a sandwich structure formed by a precursor core, a nano-oxide braided layer and a precursor shell; The molecular formula of the precursor is: M(OH)2, wherein M is selected from one or more of Ni, Co, Mn, Al, Fe, and Cu; The particle size of the precursor is 3-20 μm; the specific surface area of ​​the precursor is 10.00-14.00 m 2 / g; the tap density of the precursor is 1.90~2.20g / cm 3 ; The precursor core particle size is 1.2-10.0 μm; the thickness of the nano-oxide braided layer is 0.6-5.0 μm; The specific steps include: Step 1, according to the molar ratio of all elements in the precursor M(OH)2, prepare 2.0~8.0 mol / L mixed salt solution A, 5.0~10.0 mol / L sodium hydroxide solution B and 3.0~13.0 mol / L ammonia solution C; In step 1, the mixed salt solution A is at least one of sulfate, acetate, nitrate, and chloride; Step 2, adding pure water, sodium hydroxide solution B and ammonia solution C into the reaction kettle to prepare a reaction base liquid, and introducing nitrogen; Step 3, keeping nitrogen flowing, adding the prepared mixed salt solution A, sodium hydroxide solution B and ammonia solution C to the bottom liquid of the reactor in parallel to perform a coprecipitation reaction, controlling the reaction temperature and reaction pH, and forming a precursor core in the reactor; Step 4, when the precursor core particle size reaches the target value, stop adding solution A, solution B and solution C to the reactor, switch nitrogen to air, and carry the nano-oxide into the reactor at a fixed flow rate by air. Under the micro-oxidation of air, the primary particles become thinner and the pores become more, forming a grain boundary nano-oxide braided layer. When the nano-oxide braided layer reaches the set thickness, stop adding nano-oxide and switch to nitrogen; In step 4, the air flow rate carrying the nano-oxide is 100-300 mL / min; the nano-oxide is super-hydrophilic nano-titanium dioxide; Step 5, solution A, solution B and solution C are continuously fed and reacted to form a precursor shell, and the nano-oxide braided layer is wrapped in the middle of the particle, until the precursor particle size reaches the target particle size, the reaction feeding is stopped, and stirring and aging are continued for 3 to 4 hours; Step 6, subjecting the aged material in step 5 to solid-liquid separation, washing, and drying, and obtaining a precursor having nano-oxide grain boundary weaving after screening and demagnetization; The reaction conditions in the precursor preparation process are: at a temperature of 55-65° C., a stirring speed of 450-600±5 rpm, a pH value of 10.50-12.00, and an ammonia concentration of 0.15-0.45 mol / L until the particle size D50 of the precursor reaches the target value.

2. The method for preparing positive electrode material from grain boundary braiding precursor according to claim 1, characterized in that: The precursor is mixed with lithium hydroxide monohydrate and sintered to obtain the product; The sintering process is as follows: the molar ratio of the precursor to lithium hydroxide monohydrate is 0.95-1.10, sintering is performed at 650-800° C. for 10-30 hours, and the sintering atmosphere is an oxygen atmosphere.

Citation Information

Patent Citations

  • Titanium dioxide coated nickel-cobalt-manganese ternary positive electrode material, preparation method and application thereof

    CN111600023A

  • Crystal face induced high-nickel ternary precursor, preparation method thereof and positive electrode material

    CN113023791A